Bioassay Guided Fractionation Protocol for Determining Novel Active Compounds in Selected Australian Flora - Janice Mani; Joel Johnson; Holly Hosking; Beatriz E. Hoyos; Kerry B. Walsh; Paul Neilsen; Mani Naiker (Plants)
A large variety of unique and distinct flora of Australia have developed exceptional survival methods and phytochemicals and hence may provide a significant avenue for new drug discovery. This study proposes a bioassay guided fractionation protocol that maybe robust and efficient in screening plants with potential bioactive properties and isolating lead novel compounds. Hence, five native Australian plants were selected for this screening process, namely Pittosporum angustifolium (Gumbi gumbi), Terminalia ferdinandiana (Kakadu plum, seeds (KPS), and flesh (KPF)), Cupaniopsis anacardioides (Tuckeroo, seeds (TKS) and flesh (TKF)), Podocarpus elatus (Illawarra plum, seeds (IPS) and flesh (IPF)) and Pleiogynium timoriense (Burdekin plum, seeds (BPS) and flesh (BPF)). The methanolic extracts of the plants samples were analysed for Total phenolic content (TPC) and antioxidant capacity measure by FRAP. The highest values were found in the KPF which were 12,442 ± 1355 mg GAE/ 100 g TPC and 16,670 ± 2275 mg TXE/100 g antioxidant capacity. Extracts of GGL was deemed to be most potent with complete cell inhibition in HeLa and HT29, and about 95% inhibition in HuH7 cells. Comparative activity was also seen for KPS extract, where more than 80% cell inhibition occurred in all tested cell lines. Dose-dependent studies showed higher SI values (0.72–1.02) in KPS extracts than GGL (0.5–0.73). Microbial assays of the crude extracts were also performed against five bacterial strains commonly associated with causing food poisoning diseases were selected (Gram positive—Staphylococcus aureus and Gram negative—Escherichia coli, Salmonella typhi and Pseudomonas aeruginosa bacteria). KPF extracts were effective in suppressing microbial growth of all tested bacterial strains except for P. aeruginosa, while TKS and TKF were only slightly effective against S. aureus. Due to the potential of the GGL crude extract to completely inhibit the cells compared to KPS, it was further fractionated and tested against the cell lines. HPLC phenolic profiling of the crude extracts were performed, and numerous peak overlaps were evident in the fruit extracts. The KPF extracts demonstrated the strongest peaks which was coherent with the fact that it had the highest TPC and antioxidant capacity values. A high occurrence of t-ferulic acid in the GGL extracts was found which may explain the cytotoxic activity of GGL extracts. Peaks in KPS and KPF extracts were tentatively identified as gallic acid, protocatechuic acid, 4-hydroxybenzoic acid and syringic acid and possibly ellagic acid. HPLC time-based fractionation of the GGL extract (F1–F5) was performed and Dose dependent cytotoxic effects were determined. It was construed that F1, having the highest SI value for HeLa, HT29 and HuH7 (1.60, 1.41 and 1.67, respectively) would be promising for further fractionation and isolation process.